Simulation of Erosion Behavior of a Paraffin Plate with Particle Method. Issue 1 (1st August 2022) - Ifthacharo, M; Mustari, A P A; Permana, S; Nuril, A
Abstract: There are many mechanisms in a reactor shutdown function of MSR and inherent self-stabilization. One of those mechanisms is the fuel-salt drain system. The present study focused on the melting and solidification phenomenon that occurs in the freeze valve. An experiment was performed to investigate the erosion behavior of a solid plate by an impinging liquid to time and the effects of fluid viscosity. In addition, numerical modeling based on the MPS method to visualize the heat distribution in the plate will also be carried out. The experiment will be conducted by varying the parameters such as the liquids, temperature, and diameter. Hot water (90°C), molten paraffin, and cooking oil will be used with molded pure paraffin wax will serve as the target plates. The dimension of the target plate is cylindrical, with 44 mm in thickness and 144 mm in length for paraffin wax. The data will then be compared to the MPS simulation. The radial dispersion of the heated liquid and the temperature of the impinged liquid will affect the penetration time, hence making the formation of a mushy zone more likely and promoting the pool effect. The noticeable difference of penetration time between simulation and experiment is likely caused by the changing value of kinematic viscosity of the liquids used in different temperatures. The kinematic viscosity is set to be a constant value in the simulation.